Monetary policy and real estate asset prices in Morocco - Hassnae Hammou Ou Ali (Graduate Institute of International and Development Studies, 2025)
This study investigates the role of housing prices in the Moroccan economy and their response to monetary policy shocks. Using a Structural Vector Autoregression (SVAR) model, we explore the transmission mechanisms of monetary policy through various channels, including interest rates, credit availability, and consumer confidence. The analysis uses a comprehensive dataset spanning the period from 2006 to 2024, focusing on macroeconomic indicators, monetary policy instruments, and the Real Estate Asset Price Index (REPI). Empirical findings reveal that contractionary monetary policy leads to a delayed decline in housing prices, which may reflect structural rigidities in Morocco's real estate market. This study contributes to understanding the interplay between monetary policy and asset markets in emerging economies, providing insights for policymakers seeking to balance growth and stability objectives.
Keywords: E52; E40; R32; C32; 330; Real estate prices; Monetary policy; Interest rate; transmission channels